PENGARUH PRODUK DOMESTIK BRUTO (PDB) DAN INDEKS PEMBANGUNAN MANUSIA (IPM) TERHADAP ANGKA KEMISKINAN DI INDONESIA - Muhammad Sri Wahyudi Suliswanto (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2010)
Poverty is classic issue faced by most developing countries and is one of economic indicators to view public welfare level in any region. The research aimed to analyze effect of Gross Domestic Product (GDP), and human development index on poverty in Indonesia. Analysis used quantitative with Random Effect Model (REM) method in Panel Data with time series year 2006 to 2008. Anaysis result concluded that all independent variable simultaneously had significant effect on poverty variable in Indonesia and partially Gross Domestic Product (GDP) variable had significant negative influence on poverty with α 20%, and Human Development Index (HDI) variable had significant negative influence on poverty with α 5%.